PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 10 KEMBUNG LUAR KECAMATAN BANTAN - Siti Khomsiah; Lazim N Lazim N; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The background of the problem is low echievment in science of students IPA, can be find from students score that not complete to KKM a student (63,64), while that be able KKM 4 students (36,36) with score level 63,08. KKM that was ordinance at school is as big as 75. From that problem, so the writer have done the reseach using detailed examination methode of class (PTK). With aplication type of learning cooperative tipe examples non examples, from tech I first meeting the persentase of activity teacher 54,17% with enough category. The second meeting can be rise until / became 66,67% with good category. At tech II the first meeting 50% with enough category, and the second meeting can rise to be 58,33% with good category. At tech in first meeting the activity of the student get 70,83% with good category, and the second meeting get 83,3% with better category, the level from study of the students not be apply to 63,08% rise to 70,76 at tech I and get to be 81,15 at tech II. While the complete klasical at tech I and tech II good achieve. The aplication of cooperative learning examples non examples type to increase the student achievment in science by the fifth of SDN 10 Kembung Luar Kecamatan Bantan.Keywords : Type Cooperative Tipe Examples Non Examples, Science of IPA